2008
DOI: 10.1681/asn.2007040484
|View full text |Cite
|
Sign up to set email alerts
|

Latent TGF-β1 Protects Against Crescentic Glomerulonephritis

Abstract: Despite the critical role that TGF-␤ plays in renal fibrosis, transgenic mice that overexpress human latent TGF-␤1 in the skin exhibit normal renal histology and function even though circulating levels of latent TGF-␤1 are an order of magnitude higher than wild-type animals. In fact, latent TGF-␤1 seems to protect against renal inflammation in a model of ureteral obstruction. It is unknown, however, whether latent TGF-␤1 also has this effect in immunologically mediated forms of renal disease such as anti-GBM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 34 publications
(53 reference statements)
2
123
0
Order By: Relevance
“…7,15 Activation of TGF␤/Smad2,3 signaling during renal inflammation also produces a chemotatic effect on macrophages by inducing monocyte chemoattractant protein-1 (MCP-1)/ CCL2 expression. 16,17 Furthermore, urinary levels of TWEAK, a cytokine of the TNF superfamily, significantly increase and correlate with the activity of renal disease in patients with active lupus nephritis. 18 Exposure to TWEAK also induces MCP-1/CCL2, RANTES/CCL5, MIP-1␣/CXCL2, intraperitoneally-10/CXCL10, and SLC/CCL21 in MCs or tubular epithelial cells through a noncanonical NF-B pathway, thereby promoting leukocyte recruitment to the kidney during injury.…”
Section: Chemokines and Chemokine Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,15 Activation of TGF␤/Smad2,3 signaling during renal inflammation also produces a chemotatic effect on macrophages by inducing monocyte chemoattractant protein-1 (MCP-1)/ CCL2 expression. 16,17 Furthermore, urinary levels of TWEAK, a cytokine of the TNF superfamily, significantly increase and correlate with the activity of renal disease in patients with active lupus nephritis. 18 Exposure to TWEAK also induces MCP-1/CCL2, RANTES/CCL5, MIP-1␣/CXCL2, intraperitoneally-10/CXCL10, and SLC/CCL21 in MCs or tubular epithelial cells through a noncanonical NF-B pathway, thereby promoting leukocyte recruitment to the kidney during injury.…”
Section: Chemokines and Chemokine Receptorsmentioning
confidence: 99%
“…55,61,9 In unilateral ureteral obstruction (UUO) producing fibrosis, upregulation of tubulointerstitial MCP-1/ CCL2 correlates with degree of macrophage infiltration, which is associated with activation of the TGF␤/Smad3 signaling pathway. 16,17 TGF␤ signals through its downstream mediator, Smad3, to induce MCP-1 expression. Thus, mice deficient in Smad7, an inhibitor of TGF␤/Smad signaling, results inenhancedTGF␤/Smad3signalingthrough which MCP-1/CCL2-dependent macrophage infiltration and tubulointerstitial fibrosis develop in the UUO kidney.…”
Section: Role Of CCL and Cx3cl Chemokines In Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…37 If the inflammation persists, excessive secretion of TGF-b 1 may reduce the inflammatory response by inhibiting the production of a variety of proinflammatory cytokines and chemokines. [38][39][40] In conclusion, the present study demonstrated that: (1) antisense MCP-1 can inhibit the expression of MCP-1, but cannot reduce the expression of TGF-b 1 , which may be due to the bidirectional regulatory effect of TGF-b 1 ; and (2) antisense MCP-1 suppressed mesangial cell proliferation and mesangial matrix accumulation in anti-Thy1 MsPGN model rats, which did not entirely depend on the role of TGFb 1 and may involve other mechanisms. Therefore, our data indicate that antisense MCP-1 may be a potent therapeutic target for the treatment of MsPGN.…”
Section: Discussionmentioning
confidence: 99%
“…102,103 The overexpression of TGF-b-binding peptide, which keeps TGF-b in its latent form, has also been shown to inhibit tissue fibrosis. 104,105 This evidence indicates that blocking the TGF-b signaling pathway may be an essential therapy for tissue fibrosis.…”
Section: Perspective: Anti-fibrosis Therapymentioning
confidence: 99%